Body composition shapes cardiometabolic risk in children with multifactorial dyslipidemia - Hamou, Gaya; Ben Simon, Asaf; Yackobovitch-Gavan, Michal; Interator, Hagar; Lopez, Adar; Lubetzky, Ronit; Brener, Avivit; Lebenthal, Yael (Frontiers in Nutrition, 2026)
IntroductionChildhood-onset multifactorial dyslipidemia is associated with obesity and early cardiometabolic risk, yet weight status alone may not reflect abnormalities in body composition. We aimed to examine associations between body composition, physical activity, and cardiometabolic markers in this population.MethodsThis observational study included 101 children (mean age 13.8 ± 3.2 years) referred to a tertiary lipid clinic. Body composition was assessed by bioelectrical impedance analysis. Individuals were stratified by fat mass z-score (<2 vs. ≥2) to compare clinical characteristics. Cardiometabolic markers included blood pressure percentiles, the homeostasis model assessment of insulin resistance (HOMA-IR), and the triglyceride-to-high-density lipoprotein cholesterol (HDL-C) ratio.ResultsMost participants (67%) had obesity, high fat mass (median z-score 3.51), low muscle-to-fat ratio (z-score–1.62), and low physical activity (2 h/week). Those with fat mass z-scores ≥2 had higher blood pressure percentiles, triglycerides, HOMA-IR, and triglyceride-to-HDL-C ratios, and lower muscle-to-fat ratios (all p < 0.05). Fat mass z-score correlated with all cardiometabolic markers. In multivariable models, lower muscle-to-fat ratio (β = −15.0), lower physical activity (β = −3.1), and female sex (β = 9.9) were independently associated with higher diastolic blood pressure percentiles.DiscussionIn pediatric multifactorial dyslipidemia, both adiposity and muscle-to-fat imbalance contribute to early cardiometabolic risk and may improve risk stratification.